Normalization of Negative Stigma Against HIV/AIDS Patients: A Systematic Review of the Literature - Sutanto, Himawan; Machmud, Muslimin; Salahudin, Salahudin (University of Muhammadiyah Malang, 2023)
Human Immunodeficiency Virus (HIV)/Acquired Immunodeficiency Syndrome (AIDS) is a public health problem that stigmatizes its victims. Mental attacks, as a result of labeling and discrimination, result in psychological suffering and well-being for persons living with HIV/AIDS (PLWHA), necessitating adequate treatment. Thus, it is critical for this research to undertake a systematic assessment of scientific articles on Negative Stigma Against People Living with HIV/AIDS. This study used a descriptive analysis approach to examine publications containing the terms HIV/AIDS stigma that were published in the Scopus database between 2011 and 2018. The data is then processed and visualized using Vosviewer software, and the results show the four most dominant concepts studied by the previous author, namely human, female and human immunodeficiency virus infection. The contribution of this research is to become a reference to find out the root of the problem and the harmful impact of stigmatization on people with HIV/AIDS to help formulate recommendations for prevention and treatment that can be done (normalization). However, this research is limited because the data source only comes from Scopus. Therefore, to produce a comparative, broad, and comprehensive analysis, further studies need to include sources of other reputable international journals such as the Web of Science (WoS).